BONE MARROW TREPHINE BIOPSY: STILL A VITAL DIAGNOSTIC TOOL IN THE 21 CENTURY - Zarami AB; Bukar AA; Satumari NA (Ntec Specialist, 2017)
Trephine biopsy is an indispensable diagnostic tool in the 21 century, even though the technique has an ancient origin, its value in developing countries is still innovative. The outcome of the marrow biopsy reports are determined by many factors, which includes detailed patient clinical information, inter departmental alliance, personnel practical knowledge and technical skill. However, molecular studies on the biopsy tissues are highly necessary and that can enhance diagnostic accuracy and also aid in personalized treatment. Method: The present review is based on a comprehensive Medline literature search and multidisplinary clinical experiences of the authors'. Result: Trepanning is still new in developing countries despite its importance, these has been highlighted especially on molecular ancillary studies and quality. Conclusion: We reviewed articles on trephine biopsy and its challenges to reemphasize its usefulness as a fundamental diagnostic tool in this era. Re-examination of the reality of the test to meet the standard is what is required